2018
DOI: 10.26487/hebr.v2i1.1465
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Utaut Factors on E-Retention With E-Satisfaction as Mediating Variable in E-Learning

Abstract: Factors on Unified Theory of Acceptance and Use of Technology (UTAUT) are factors derived from UTAUT technology acceptance model, which is used to describe the factors that influence the acceptance of individuals on the implementation of a new technology in the enterprise. This study aimed to analyze the influence of UTAUT factors on E-retention with E-satisfaction as mediating variable. This study uses a quantitative approach with the total samples. The results showed that: (1) Performance Expectancy influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…The effort expectancy construct in each model is significant, both in the context of voluntary and mandatory use. However, it is significant only during the first period, and becomes insignificant again over a period of extended and sustained use (Agustina & Indriati, 2018).…”
Section: Effort Expectancymentioning
confidence: 97%
See 1 more Smart Citation
“…The effort expectancy construct in each model is significant, both in the context of voluntary and mandatory use. However, it is significant only during the first period, and becomes insignificant again over a period of extended and sustained use (Agustina & Indriati, 2018).…”
Section: Effort Expectancymentioning
confidence: 97%
“…However, there are also those who find that Performance Expectancy does not have a significant effect on user satisfaction (Hutabarat & Jambi, 2020). Performance Expectancy, Effort Expectancy partially do not have a significant effect on E-satisfaction (Agustina & Indriati, 2018).…”
mentioning
confidence: 99%
“…The main objective of UTAUT is to give an understanding of the usage reaction to new technology introduction (Handayani and Sudiana, 2015). UTAUT has been developed through the acceptance of eight model theories in the information research area (Agustina and Indriati, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The facilitating condition describes the resources and supports that people have in affecting the intention to use a particular technology, and it is similar to the one that influences the actual usage of technology (Kasri and Yuniar, 2021;Venkatesh et al, 2003). Some previous studies showed the positive impact of facilitating conditions to intent on the usage of technology (Agustina and Indriati, 2018;Kasri and Yuniar, 2021;Rachmat et al, 2020). However, a study by Sulaeman and Ninglasari (2020) did not find any significant influence from facilitating conditions toward intention to use online platforms model for zakat payment.…”
Section: Facilitating Condition and Intention To Use Digital Online P...mentioning
confidence: 99%
“…Studi yang menggunakan faktor TAM untuk memprediksi e-satisfaction antara pengguna e-learning sangat terbatas karena sebagian besar studi yang ada berkonsentrasi pada niat (Boon-itt, 2015;Headar et al, 2013;Ilgaz & Gülbahar, 2015;Indriati & Agustina, 2018). Beberapa penelitian yang menilai kepuasan menggunakan determinan kualitas layanan seperti keandalan, daya tanggap, personalisasi, keamanan, kepercayaan, interaktivitas dan aksesibilitas, yang bukan merupakan variabel TAM.…”
Section: Pendahuluanunclassified